Penerapan Sanitasi di Lingkungan Kerja Fisik Main Kitchen Verwood Hotel & Serviced Residence Surabaya - Bagas Karunia Putra; Niken Purwidiani; Lilis Sulandari; Ila Huda Puspita Dewi (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
Sanitation in the main kitchen work environment of a hotel is a crucial factor in ensuring food safety and worker health. The Main Kitchen at Verwood Hotel & Serviced Residence Surabaya has a high level of activity in food processing, making proper sanitation essential. This study aims to analyze the implementation of sanitation in the physical work environment of the Main Kitchen at Verwood Hotel & Serviced Residence Surabaya, focusing on the condition of the floors, walls, ceiling, ventilation, and lighting. This research uses a qualitative descriptive method, with data collection techniques including direct observation, interviews with kitchen staff, and documentation. The findings indicate several sanitation challenges, such as cracked floors and water puddles due to an inadequate drainage system, walls requiring regular maintenance, and a leaking ceiling that poses a risk of pest infestation. Additionally, the ventilation system is not yet optimal in reducing smoke and humidity, while lighting remains uneven in some areas. Based on these findings, infrastructure improvements are recommended, including drainage system upgrades, wall maintenance, and ceiling repairs. Moreover, optimization of ventilation and lighting and regular sanitation monitoring should be conducted to ensure the kitchen maintains high cleanliness standards. By implementing these measures, the kitchen work environment is expected to become more hygienic, safe, and supportive of food quality.